Novel dysregulated long non‐coding RNAs in the acute kidney injury‐to‐chronic kidney diseases transition unraveled by transcriptomic analysis - Bhupendra Puri; Syamantak Majumder; Anil Bhanudas Gaikwad (Pharmacology Research & Perspectives)
Abstract Acute kidney injury (AKI)‐to‐chronic kidney disease (CKD) transition involves a complex pathomechanism, including inflammation, apoptosis, and fibrosis where long non‐coding RNAs (lncRNAs) play a crucial role in their regulation. However, to date, only a few lncRNAs have been discovered to be involved in the AKI‐to‐CKD transition. Therefore, this study aims to investigate the dysregulated lncRNAs in the AKI‐to‐CKD transition in vitro and in vivo. To mimic AKI‐to‐CKD transition both in vivo and in vitro, bilateral ischemia‐reperfusion (IR) kidney injury was performed in Wistar rats (male), and normal rat kidney epithelial cell (NRK52E) cells were treated with exogenous transforming growth factor‐β1 (TGF‐β1). Further processing and analysis of samples collected from these studies (e.g., biochemical, histopathology, immunofluorescence, and RNA isolation) were also performed, and transcriptomic analysis was performed to identify the dysregulated lncRNAs. Rats subjected to IR showed a significant increase in kidney injury markers (creatinine, blood urea nitrogen (BUN), kidney injury molecule‐1(KIM‐1), and neutrophil gelatinase‐associated lipocalin (NGAL) along with altered cell morphology). Apoptosis, inflammation, and fibrosis markers were markedly increased during the AKI‐to‐CKD transition. Furthermore, transcriptomic analysis revealed 62 and 84 unregulated and 95 and 92 downregulated lncRNAs in vivo and in vitro, respectively. Additionally, functional enrichment analysis revealed their involvement in various pathways, including the tumor necrosis factor (TNF), wingless‐related integration site (Wnt), and hypoxia‐inducible factor‐1 (HIF‐1) signaling pathways. These identified dysregulated lncRNAs significantly contribute to AKI‐to‐CKD transition, and their knockin/out can aid in developing targeted therapeutic interventions against AKI‐to‐CKD transition.